Spectroscopic and ab initio investigation of 2,6-difluorophenylacetylene-amine complexes: coexistence of C-H center dot center dot center dot N and lone-pair center dot center dot center dot pi complexes and intermolecular coulombic decay - Mondal, Sohidul Islam; Dey, Arghya; Sen, Saumik; Patwari, G. Naresh; Ghosh, Debashree (Physical Chemistry Chemical Physics, 2015)
Binary complexes of 2,6-difluorophenylacetylene with methylamine, dimethylamine, trimethylamine and triethylamine were investigated using one colour resonant two photon ionization and infrared-optical double resonance spectroscopic techniques combined with high level ab initio calculations. All four amines form C-Ac-H center dot center dot center dot N hydrogen-bonded complexes. Additionally trimethylamine and triethylamine form complexes characterized by Lp center dot center dot center dot pi interactions, due to the electron deficient nature of the phenyl ring of 2,6-difluorophenylacetylene. The Lp center dot center dot center dot pi interacting structure of the 2,6-difluorophenylacetylenetrimethylamine complex is about 1.5 kJ mol(-1) higher in energy than the C-Ac-H center dot center dot center dot N hydrogen-bonded structure, which is the global minimum. Energy decomposition analysis indicates that the electrostatics and dispersion interactions favour the formation of C-Ac-H center dot center dot center dot N and Lp center dot center dot center dot pi complexes, respectively. Interestingly the C-Ac-H center dot center dot center dot N hydrogen-bonded complex of 2,6-difluorophenylacetylene-triethylamine showed a smaller shift in the acetylenic C-H stretching frequency than the 2,6-difluorophenylacetylene-trimethylamine complex. The observed fragmentation of the binary complexes of 2,6-difluorophenylacetylene with the four amines following resonant two-photon ionization can be explained on the basis of the intermolecular coulombic decay process.